ANALISA KEGAGALAN PIPA ASTM A179 PADA RUANG BAKAR BOILER - Nasution, Fadly Ahmad Kurniawan; Irawan, Ade (JiTEKH, 2020)
A steam power plant or better known as a boiler or steam boiler, the steam boiler itself has the main components, namely the pipe used to circulate water, the pipe itself is made of metal material, the operation of the boiler, the pipe in the boiler combustion chamber experiences a change in temperature which resulted in a deformation that resulted in a change in the mechanical properties of the pipe material. This chapter will explain the steps taken in carrying out several tests with the aim of knowing the hardness of the boiler pipe material. The tests carried out are testing the microstructure, and the hardness value, which will be explained in the flow chart in the sub-chapter below. The hardness decreased, at a load of 1500 kgf. The hardness value decreased not too significantly, from 132.1667 to 91.81667 BHN. That the decrease in hardness is only 0.43% Obtained the standard average hardness value in the boiler with each brinell test, amounting to 132.1667 BHN Obtained the average hardness value which is affected by the temperature of the boiler combustion chamber with each brinell test, amounting to 91.71667 HRB, Based on the value of the hardness test results compared to that after heating experienced a decrease in hardness in the brinell test by 0.43%.